2015
DOI: 10.1007/s10803-015-2565-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered Dynamics of the fMRI Response to Faces in Individuals with Autism

Abstract: Abnormal fMRI habituation in autism spectrum disorders (ASD) has been proposed as a critical component in social impairment. This study investigated habituation to fearful faces and houses in ASD and whether fMRI measures of brain activity discriminate between ASD and typically developing (TD) controls. Two identical fMRI runs presenting masked fearful faces, houses, and scrambled images were collected. We found significantly reduced habituation to fearful faces but not houses in ASD. In addition, amygdala hab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(57 citation statements)
references
References 79 publications
(86 reference statements)
3
53
1
Order By: Relevance
“…Examples of these social interaction impairments among people with ASD include theory of mind, empathy, and facial emotion recognition (Simon Baron-Cohen, Leslie, & Frith, 1985; S. Baron-Cohen & Wheelwright, 2004; Uljarevic & Hamilton, 2013). Consistent with the findings that such social interactions depend on the social brain neural system (Adolphs, 2009), abnormalities within the social brain have been observed among individuals with ASD (Yuta Aoki, Cortese, & Tansella, 2015; Kana, Keller, Cherkassky, Minshew, & Just, 2009; Kleinhans, Richards, Greenson, Dawson, & Aylward, 2016; Murphy et al, 2017; Pelphrey, Shultz, Hudac, & Vander Wyk, 2011). Besides the anatomical extension of abnormalities, individuals with ASD consistently present atypical functional connections (FCs) (Cherkassky, Kana, Keller, & Just, 2006; Di Martino et al, 2014; Uddin, Supekar, & Menon, 2013).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Examples of these social interaction impairments among people with ASD include theory of mind, empathy, and facial emotion recognition (Simon Baron-Cohen, Leslie, & Frith, 1985; S. Baron-Cohen & Wheelwright, 2004; Uljarevic & Hamilton, 2013). Consistent with the findings that such social interactions depend on the social brain neural system (Adolphs, 2009), abnormalities within the social brain have been observed among individuals with ASD (Yuta Aoki, Cortese, & Tansella, 2015; Kana, Keller, Cherkassky, Minshew, & Just, 2009; Kleinhans, Richards, Greenson, Dawson, & Aylward, 2016; Murphy et al, 2017; Pelphrey, Shultz, Hudac, & Vander Wyk, 2011). Besides the anatomical extension of abnormalities, individuals with ASD consistently present atypical functional connections (FCs) (Cherkassky, Kana, Keller, & Just, 2006; Di Martino et al, 2014; Uddin, Supekar, & Menon, 2013).…”
Section: Introductionsupporting
confidence: 76%
“…Since not all individuals with the endophenotype develop ASD clinical diagnosis (Ozonoff et al, 2011), the neural correlates for the endophenotype and the diagnosis may differ. Although we did not investigate the neural correlates for the diagnosis because of the small sample size, neural correlates for the clinical diagnosis of ASD might be located within the social brain (Yuta Aoki et al, 2015; Kana et al, 2009; Kleinhans et al, 2016; Murphy et al, 2017; Pelphrey et al, 2011). Given that there was no significant difference in the WLS of the selected FCs between individuals with ASD and their unaffected siblings, the selected FCs represent the ASD endophenotype, rather than the ASD diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, the idea that the amygdala may be a site for sex-specific action of OT could be of relevance for the treatment of sex-biased psychiatric disorders of social dysfunction. Indeed, altered amygdala functioning is a main characteristic of autism spectrum, social anxiety, and borderline personality disorders (Baron-Cohen et al, 2000; Kleinhans et al, 2016; Kim et al, 2015; Evans et al, 2008; Goldin et al, 2009; Bruhl et al, 2014; Donegan et al, 2003; Herpertz et al, 2001) and has been found to be normalized in response to intranasal OT (Domes et al, 2013; Bertsch et al, 2013; Labuschagne et al, 2010). Therefore, it is imperative to further understand the sex-specific role of the OT system in the amygdala and its subregions in the regulation of social behavior in both rodents and humans.…”
Section: Discussionmentioning
confidence: 99%
“…We chose to measure habituation and initial sensitivity to stimulation because habituation learning is impaired in individuals with ASD, and abnormalities in tactile sensitivity are present in >95% of cases. 2,[69][70][71][72][73][74][75][76][77] The degree of habituation impairment in ASD patients also correlates with the severity of social impairment, and recent studies in monogenic mouse models of ASD suggest peripheral tactile hypersensitivity and impaired habituation precede, and may even lead, to more complex cognitive and social impairments. 70,78 To analyze the data we wrote custom scripts to extract 26 quantitative phenotypic features that fall into 5 categories of morphology, baseline locomotion, initial sensitivity, habituation learning, and spontaneous recovery/short-term memory retention (Figure 1J and see Methods and Table S2 for a complete description of phenotypic features).…”
Section: Asd-associated Genes Are Highly Conserved To C Elegansmentioning
confidence: 99%